Forward-viewing photoacoustic imaging probe with bundled ultra-thin hollow optical fibers. (14th June 2016) - Seki, A; Iwai, K; Katagiri, T; Matsuura, Y
Abstract: A photoacoustic imaging system composed of a flexible bundle of thin hollow-optical fibers is proposed for endoscopic diagnosis. In this system, a bundle of 127 hollow-optical fibers with an inner diameter of 100 μ m was fabricated. The total diameter of the bundle was 2.1 mm, and the minimum bending radius was around 10 mm. Owing to the small numerical aperture of hollow optical fibers, a high resolution image was obtained without using a lens array at the distal end. In the imaging system, the hollow fibers in the bundle were aligned at the input end, so the hollow fibers were sequentially excited by linearly scanning the laser beam at the input end. Photoacoustic imaging systems consisting of the bundled fibers for excitation of acoustic wave and piezoelectric probes for detection of photoacoustic signals were built. By using the systems, photoacoustic images of blood vessels in the ovarian membrane of fish were taken to test the feasibility of the system. As a result, photoacoustic images of the vessel were successfully obtained with a laser fluence of around 6.6 mJ cm −2 .